In-situ electro-stimulation enhanced branching but not massive scleractinian coral growth - Samidon, Munandar; Razi, Nanda Muhammad; Agustiar, Muhammad; Harahap, Puad Batari; Najmi, Nurul; Bahri, Samsul; Liu, Shang Yin Vanson (Frontiers in Marine Science, 2022)
Calcium carbonate (CaCO3) is the main component of the skeleton of scleractinian corals and is a preferable substrate for attachment and growth. An electro-stimulation method based on the electrolysis of seawater, which generates calcium and magnesium minerals as a crystalline coating over artificial metal structures, was used to boost coral growth during the 1970s. Few studies have attempted to compare survival and growth between electro-stimulated corals and non-electro-stimulated corals in situ. In this study, we used 2D image analysis to quantify the growth of branching and massive corals on electro-stimulated structures. Among four metallic structures that were deployed in Sabang, Aceh, Indonesia, three were electro-stimulated (12 V) and one was used as a control. Two branching corals (Acropora gemmifera and Pocillopora verrucosa) and two massive coral species (Porites murrayensis and Porites lobata) were selected. A total of 256 fragments, comprising 128 fragments derived from two branching species and 128 fragments derived from two massive species, were randomly dispatched to each structure. Underwater photographs were taken at three intervals from August 2019 to December 2020. The results showed that the survival rates (excluding lost fragments) of branching corals under electro-stimulation were approximately 19% higher than massive. However, no significant difference was found between the survival rates of the treatment and control groups for both branching and massive corals. Furthermore, we found that under electro-stimulation, branching corals grew faster than controls but not massive. Our study provides pieces of evidence for the potential use of electrochemical processes in stimulating the growth of branching corals.